Drug Control Policy, Normalization, and Symbolic Boundaries in Amsterdam's Coffee Shops. (29th August 2020) - Dickinson, Timothy; Jacques, Scott
Abstract: This study examines the relationship between drug control policy, normalization and symbolic boundary work among drug traders. Taking from interviews with 50 personnel in Amsterdam's coffee shops, we find that Dutch drug policy shapes their understanding of what comprises morally acceptable drug use and sales. Conversely, the rules set by the state also guide personnel's definitions of what is morally unacceptable: using hard drugs or committing predatory crimes. To normalize their own involvement with cannabis, personnel must identify potential rule breakers and criminals. To do so, they construct symbolic boundaries differentiating themselves from these persons. We conclude by discussing the theoretical implications of our findings for normalization and symbolic boundaries and by suggesting a potential negative secondary impact of cannabis decriminalization or legalization: the further marginalization of hard drug users.